Amelioration of Carcinogen-Induced Toxicity in Mice by Administration of a Potentized Homeopathic Drug, Natrum Sulphuricum 200. Issue 1 (2009) - Bhattacharjee, Nandini; Pathak, Surajit; Khuda-Bukhsh, Anisur Rahman
Abstract : To examine if a potentized homeopathic drug, Natrum Sulphuricum 200 (Nat Sulph-200) has protective potentials against hepatocarcinogenesis, liver tumors were induced in mice through chronic feeding of P -dimethylaminoazobenzene (p-DAB; initiator of hepatocarcinogenesis) and phenobarbital (PB; promoter). Mice were divided into five sub-groups: fed normal low protein diet (Gr. I, normal control); fed normal low protein plus alcohol-200 (vehicle of the homeopathic remedy) (Gr. II); fed diet mixed with 0.06% p-DAB plus 0.05% PB (Gr. III); fed diet and carcinogens like Gr.III, plus alcohol 200 (positive control for drug fed mice) (Gr. IV) and fed diet and carcinogens like Gr. III, plus Natrum Sulphuiricum-200 (Gr. V; drug fed). Mice were sacrificed at day 7, 15, 30, 60, 90 and day 120 for study of cytogenetical endpoints like chromosome aberrations (CA), micronuclei (MN), mitotic index (MI) and sperm head anomaly (SHA) and biochemical toxicity parameters like aspartate amino transferase (AST), alanine amino transferase (ALT), acid (AcP) and alkaline (AlkP) phosphatases, lipid peroxidation (LPO) and reduced glutathione (GSH) content. Less number of liver tumors were observed in Gr. V (drug fed) mice. Administration of Nat Sulph 200 reduced genomic damage, activities of AcP, AlkP, AST, ALT, LPO and increased GSH content. Therefore, independent replication of the study by others is encouraged.